Deteksi Penyakit Citrus Vein Phloem Degeneration (CVPD) Dengan Teknik Polymerase Chain Reaction (PCR) pada Daun Tanaman Jeruk Yang Memiliki Pola Gejala Klorosis Berbeda - MELANI, RIDA; ADIARTAYASA, WAYAN; WIJAYA, I NYOMAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.7, No.2, April 2018, 2018)
Citrus Vein Phloem Degeneration (CVPD) Disease Detection With Polymerase Chain Reaction (PCR) Technique In Citrus Plant Leaves That Have Different Chlorosis Symptom Patterns Detection of Citrus Vein Phloem Degeneration (CVPD) disease with Polymerase Chain Reaction (PCR) on citrus leaves that have different pattern of chlorosis symptoms was conducted at laboratory of Genetic Resources and Biology Molecular, Udayana University. This study aims to determine the presence of Liberibacter asiaticus in citrus leaves that have different patterns of chlorosis symptoms using a specific primer 16S rDNA (OI1 and OI2c). DNA amplified on 1% agarose gel obtained DNA bands of 1160 bp on four samples with a pattern of symptoms of chlorosis.